Chemical Extraction of Microorganisms from Water‐Saturated, Packed Sediment. (1st June 2013) - Ugolini, Fabio; Schroth, Martin H.; Bürgmann, Helmut; Hammes, Frederik; Zeyer, Josef
Abstract : Microbial characterization of aquifers should combine collection of suspended and attached microorganisms (biofilms). This study investigated chemical extraction of microorganisms from water‐saturated, packed sediment containing established biofilms. It compares the use of different detachment‐promoting agent (DPA) solutions with tap water as eluent in column experiments. Extraction efficiency was determined from cell concentrations in the column effluent. Adenosine triphosphate concentrations were measured to confirm cell extraction and as an indicator of cell membrane integrity. Quality of extracted bacterial communities was assessed by comparing their terminal restriction fragment length polymorphism profiles with destructively sampled sediment‐community profiles. Extraction efficiency increased more than 8‐fold when deionized water, D‐amino acids, or enzymes were used as a DPA. Community profiles recovered by individual DPA solutions showed more pronounced differences at the level of rare microbial groups, whereas abundant groups appeared ubiquitous across treatments. These results suggest that comparison of communities extracted by different DPAs can provide improved information on the occurrence of rare microbial groups in biofilms.